Reconstructing the Principle of Due Process of Law in Automated Public Decision-Making in Digital Public Services - Muhammad Suhardi (Yayasan Hisnul Muslim Lombok, 2026)
This study examines the reconstruction of the principle of due process of law in automated public decision-making within digital public services in Indonesia. The objective is to analyze how citizens’ procedural rights should be protected when public service decisions are made, supported, or significantly influenced by algorithmic systems. This research employs a qualitative legal method with a normative-juridical and conceptual approach. Data were collected through documentary study of Indonesian legal instruments concerning government administration, public services, personal data protection, electronic systems, and electronic-based government, supported by relevant scholarly literature on automated decision-making, administrative law, and algorithmic accountability. The findings show that Indonesia’s current legal framework provides general principles of legality, accountability, public service obligations, and data protection, but has not yet specifically regulated the procedural consequences of automated public decision-making. This regulatory gap may weaken citizens’ ability to understand, correct, question, and challenge algorithm-based public service decisions. The study proposes an algorithmic due process framework consisting of five core rights: the right to notification, the right to explanation, the right to data correction, the right to meaningful human review, and the right to administrative or judicial challenge. This study contributes to administrative law scholarship by linking classical due process principles with algorithmic governance in digital public services.